Central Plains Experimental Range long term ecological research: site review, June 1989 - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 1989)
Our approach to the LTER program has explicitly considered system behavior across a range of spatial and temporal scales. Our work has spanned spatial scales from individual plants to the central grassland region of the United States, focusing on annual to century level implications. In our approach to LTER we assumed that an important criterion for judging the significance of our LTER-funded work at the Central Plains Experimental Range would be our ability to generalize results beyond the boundaries of the site. Because we are interested in spatial and temporal scales that exceed the boundaries of a single site, we have emphasized observations and experiments with a spatially explicit dimension, as well as technologies to deal with the analysis and extrapolation of spatial information. These technologies include simulation modeling and geographic information systems.
Site review June 1989
SGS-LTER 1989 CPER site review
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: grassland ecology; long term ecological research; shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland